Design de procedimentos e postos de trabalho: o uso da análise ergonômica e o método OCRA - Silva, Fernando Partica da (2013)
The industrial sector is responsible for a high number of working stations which require a lot of repetitive actions, mainly of the upper limbs, resulting in an increasing number of Work Related Musculo Skeletal Disorders (WMSD). The prevention of WMSD, can be promoted by the application of management measures and diagnostic of risk situations in real working conditions, through the use of ergonomic tools to fully evaluate the main risk factors for the occurrence of WMSD. This study employed the OCRA Method as an ergonomic tool in a Metal-Mechanics sector industry and aimed to promote ergonomic improvements and verify the influence of productivity levels in a redesigned working station. The OCRA Check List enabled to map the Paint Sector Jobs and characterize the working station with the highest repetitive action musculoskeletal embarassment. The OCRA Index allowed to identify and quantify risk factors, and predict WMSD occurrences before and after the redesign of Painter I procedures and working stations. Painter I worker productivity was measured and it was observed that the ergonomic improvements provided by OCRA Method influenced the worker productivity. The use of OCRA Method and its guidelines for ergonomic interventions to the redesign of procedures and working stations, resulted in a reduction from to 15.36 to 2.03 in the OCRA Index, which corresponded to four times decrease in the probability of workers presenting occupational disease caused by repetitive actions. The working station redesign positively interfered in the work productivity since the reduction of technical actions and improvement of posture conditions resulted in decrease in consumption of paint used on the Profile C metallic parts; monthly, ergonomic redesign, besides creating better working conditions, enable through productivity gains, savings in more than 145 paint per month for the Painter I working station, without affecting the quality of the procedure. The OCRA Method application, a method recognized and recommended by the international standards ISO and EN, provided the interface of the ergonomic method to the redesign of procedures and working stations, aiming at ergonomic improvements and productivity gains in the workplace under study.